Advances in the treatment of cervical rheumatoid: Less surgery and less morbidity - Mallory, Grant W (Baishideng Publishing Group Inc, 2014)
Rheumatoid arthritis is a chronic systemic inflammatory disease that often affects the cervical spine. While it was initially thought that cervical involvement was innocuous, natural history studies have substantiated the progressive nature of untreated disease. Over the past 50 years, there has been further elucidation in the pathophysiology of the disease, as well as significant advancements in medical and surgical therapy. The introduction of disease modifying drugs and biologic agents has reduced the amount of patients with advanced stages of the disease needing surgery. Advancement in instrumentation techniques has improved patient outcomes and fusion rates. The introduction of endoscopic approaches for ventral decompression may further lower surgical morbidity. In this review, we give a brief overview of the pertinent positives of the disease. A discussion of historical techniques and the evolution of surgical therapy into the modern era is provided. With improved medical therapies and less invasive approaches, we will likely continue to see less advanced cases of disease and less surgical morbidity. Nonetheless, a thorough understanding of the disease is crucial, as its systemic involvement and need for continued medical therapy have tremendous impact on overall complications and outcomes even in patients being seen for standard degenerative disease with comorbid rheumatoid.